The history of embalming in the era of anatomists of the XV-XVIII centuries - Svetlana Ninelievna Chilingaridi; Sergey Evgenievich Shemyakov; Vladimir Yefimovich Milyukov; Elena Evgenevna Nikiforova; Kheyalya Murshud Kizi Sharifova; Elshan Rovshan Oglu Sharifov; Cao Cuong Nguyen (International Journal of Human Anatomy, 2023)
A historical review traces embalming practices and their role in anatomical study between the 15th and 18th centuries, connecting technique evolution to scientific milestones and ethics.